TINJAUAN HUKUM ISLAM TERHADAP KEWAJIBAN PENGGUNAAN PRODUK LOKAL BAGI INSTANSI PEMERINTAH (Studi Inpres. No. 2/2009 Tentang Peningkatan Penggunaan Produk Dalam Negeri (P3DN) - Rahman, Miftahur (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2019)
President No instructions. 2 / 2009 About Improving Use of Domestic Products (P3DN) was born on February 9, 2009. This dilatarr back on the number of imported products flooding into the local market that triggered a global crisis. In addition, people’s purchasing power is still relatively low stock contributed to beauty product market is relatively cheap imports. In the instructions the President No. 2 I 2009 on Better Use of Domestic Products (P3DN) and the Islamic concept of this requires government agencies to consume local products. This calls for the author’s attention to research on instruction Presidential No. 2 I 2009 on Better Use of Domestic Products (P3DN), the extent to which if the instructions are analyzed by the President of Islamic law in the case of an obligation for government agencies to consume local products. This study was designed to use different types of literature research (library research) is by way of an inventory and classify the application of literature instruction Presidential No. 2 / 2009 on Better Use of Domestic Products (P3DN) and scripture al-Quran and Islamic principles that are relevant to this discussion. Liabilities use of local products is part of the instructions the President No. 2 I 2009 on Better Use of Domestic Products (P3DN). In analyzing the data, the author qualitative research methods. Namely President No. analyze instructions. 2 / 2009 on Better Use of Domestic Products (P3DN) with consumption in the Islamic theory in order to obtain the expected results. With this qualitative research methods to produce the conclusion that the provisions of Presidential Decree No. instructions. 2 / 2009 on Better Use of Domestic Products (P3DN) according to Islam is a deprivation of voting rights for citizen consumption activities, which contrary to the principles of Islam mu’amalah namely ‘an-Taradhin (compliance).